Dissolution and reduction of cobalt ions in the polyol process using ethylene glycol: identification of the active species and its role1. (2nd June 2015) - Matsumoto, Takatoshi; Takahashi, Kazuma; Kitagishi, Keisuke; Shinoda, Kozo; Cuya Huaman, Jhon L.; Piquemal, Jean-Yves; Jeyadevan, Balachandran
<x xml:space="preserve">Abstract</x> The monoanionic state of ethylene glycol was theoretically and experimentally confirmed to be the active species during reduction reaction of metal salts.